Rebuttal to review of Bernard V. Bothmer, Egyptologist in the Making, 1912 through July 1946 - Eaton-Krauss, Marianne.
Rebuttal to review of Bernard V. Bothmer, Egyptologist in the Making, 1912 through July 1946 (JARCE 56 [2020], 254–56).